Bending of Adenovirus Origin DNA by Nuclear Factor I as Shown by Scanning Force Microscopy Is Required for Optimal DNA Replication - Mysiak, Monika E. (American Society for Microbiology, 2004)
Nuclear factor I (NFI) is a transcription factor that binds to the adenovirus type 5 (Ad5) origin of replication and recruits the adenovirus DNA polymerase, thereby stimulating initiation of DNA replication in vitro. Using scanning force microscopy, we demonstrate that NFI induces a 60° bend upon binding to the origin. The A/T-rich region preceding the core recognition sequence of NFI influences the DNA bend angle, since substitution of A/T base pairs by G/C base pairs severely decreases bending. Mutations in the A/T-rich region do not affect binding of NFI to DNA. However, mutations that reduce the protein-induced bend lead to a loss of NFI-stimulated replication, indicating that DNA bending is functionally important. In contrast, basal initiation or DNA binding of the polymerase is not impaired by these origin mutations. We conclude that binding of NFI to the Ad5 origin causes structural changes in DNA that are essential for the stimulatory function of NFI in replication. We propose that NFI-induced origin bending facilitates the assembly of a functional initiation complex.